Effects of anoxia, aglycemia, and acidosis on cytosolic Mg2+, ATP, and pH in rat sensory neurons. - Henrich, M; Buckler, K (2008)
Sensory neurons can detect ischemia and transmit pain from various organs. Whereas the primary stimulus in ischemia is assumed to be acidosis, little is known about how the inevitable metabolic challenge influences neuron function. In this study we have investigated the effects of anoxia, aglycemia, and acidosis upon intracellular Mg(2+) concentration [Mg(2+)](i) and intracellular pH (pH(i)) in isolated sensory neurons. Anoxia, anoxic aglycemia, and acidosis all caused a rise in [Mg(2+)](i) and a fall in pH(i). The rise in [Mg(2+)](i) in response to acidosis appears to be due to H(+) competing for intracellular Mg(2+) binding sites. The effects of anoxia and aglycemia were mimicked by metabolic inhibition and, in a dorsal root ganglia (DRG)-derived cell line, the rise in [Mg(2+)](i) during metabolic blockade was closely correlated with fall in intracellular ATP concentration ([ATP](i)). Increase in [Mg(2+)](i) during anoxia and aglycemia were therefore assumed to be due to MgATP hydrolysis. Even brief periods of anoxia (<3 min) resulted in rapid internal acidosis and a rise in [Mg(2+)](i) equivalent to a decline in MgATP levels of 15-20%. With more prolonged anoxia (20 min) MgATP depletion is estimated to be around 40%. With anoxic aglycemia, the [Mg(2+)](i) rise occurs in two phases: the first beginning almost immediately and the second after an 8- to 10-min delay. Within 20 min of anoxic aglycemia [Mg(2+)](i) was comparable to that observed following complete metabolic inhibition (dinitrophenol + 2-deoxyglucose, DNP + 2-DOG) indicating a near total loss of MgATP. The consequences of these events therefore need to be considered in the context of sensory neuron function in ischemia.